Effect of Dietary Clostridium butyricum Supplementation on Growth Performance, Intestinal Barrier Function, Immune Function, and Microbiota Diversity of Pekin Ducks - Liu, Yanhan; Liu, Cun; An, Keying; Gong, Xiaowei; Xia, Zhaofei (Animals (Basel), 2021)
Clostridium butyricum (C. butyricum) is increasingly being used to test the promotion of the gut health of animals. However, the modes of action for such applications for waterfowl remain unclear. Thus, we investigated whether or not intestinal barrier function, immune-related gene expression, and the diversity of the intestinal microbiota in Pekin ducks varied under C. butyricum supplementation. A total of 500 ducks were randomly assigned into five treatments supplemented with basal diets containing: either 0 (group Control), 200 (group CB200), 400 (group CB400) and 600 (group CB600) mg/kg C. butyricum or 150 mg/kg aureomycin (group A150) for 42 days. In comparison with the control group, C. butyricum supplementation enhanced the growth performance and intestinal villus height of Pekin ducks at 42 d. Serum immune indexes and fecal short-chain fatty acids (SCFAs) were all improved at both 21 d and 42 d after C. butyricum addition. The mRNA expression levels of Mucin2, Zonula occludens-1 (ZO-1), Caudin-3, and Occludin increased at 21 d and 42 d and the mRNA expression levels of IL-4 and IL-10 only increased at 42 d after C. butyricum addition. Dietary C. butyricum also resulted in an increase in the number of diversities of operational taxonomic units (OTUs), and an increase in the α-diversity of intestinal microbiota. The addition of C. butyricum altered the composition of the intestinal microbiota from 21 d to 42 d. The relative abundance of Firmicutes and Bacteroidetes showed little changes among groups; however, the relative abundance of Firmicutes/Bacteroidetes were found to have been significantly different between the 21 d and 42 d. C. butyricum administration improved the intestinal health of Pekin ducks by increasing the diversity of intestinal microbiota, enhancing the SCFAs contents, and strengthening the intestinal barrier function and immune systems. The optimal dietary supplementation dosage was recommended as 400 mg/kg in the diet.